2016
DOI: 10.1042/bcj20160544
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biophysical analysis of nuclease protein antibiotics

Abstract: Protein antibiotics (bacteriocins) are a large and diverse family of multidomain toxins that kill specific Gram-negative bacteria during intraspecies competition for resources. Our understanding of the mechanism of import of such potent toxins has increased significantly in recent years, especially with the reporting of several structures of bacteriocin domains. Less well understood is the structural biochemistry of intact bacteriocins and how these compare across bacterial species. Here, we focus on endonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…4D to F). These observations are in line with the generally high specificity and selectivity of immunity partners in silencing toxin functions (14,(44)(45)(46).…”
Section: Resultssupporting
confidence: 81%
“…4D to F). These observations are in line with the generally high specificity and selectivity of immunity partners in silencing toxin functions (14,(44)(45)(46).…”
Section: Resultssupporting
confidence: 81%
“…The present analysis places these NBs in group I, which also includes NBs from Klebsiella pneumoniae , Serratia marcescens , Shigella sonnei , Enterobacter cloacae , Xenorhabdus , and Citrobacter ( Fig 3 ). Structures for both the rRNase NB ColE3 and DNase NB ColE9 from this group have been reported [ 56 ], plus there have been numerous biophysical and structural studies of other NBs from this group [ 57 ]. The main structural features of group I NBs are a T-domain composed of a disordered N-terminal region adjoining a folded domain, the latter identified in the PFAM database as PFAM 03515, and a central coiled-coil region which constitutes the R-domain.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] previously highlighted a similar region in a few nuclease pyocins and colicins the deletion of which abolished cytotoxic activity [ 74 ]. The structures of three NB T-domains are known (annotated in the PFAM database as PFAM 03515); colicin E3 (2B5U), colicin E9 (5EW5 [ 56 ]) and the S-type pyocin domain from Erwinia carotovora (3MFB) as well as the T-domain of the pore forming colicin B (1RH1) which shares high sequence identity to the T-domain of the NB colicin D. We performed structure-based sequence alignments and found that the DPY motif is integral to a much larger segment spanning the C-terminal half (~140 amino acids) of the T-domain ( Fig 4b ). This segment (coloured blue in Fig 4b ) is identified in the PFAM database as the pyocin_s domain (PFAM 06958) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Vibrio vulnificus nuclease (Vvn) ( 21 ) and endonuclease I ( 22 ) retain a big α-helical domain located at the C-terminus sheltering the central His-Me finger nuclease (Figure 3C ), whereas toxins (e.g. Colicin E9 ( 40 ), Pyocin S2 ( 41 )) possess expanded structural decorations at the N-terminus.…”
Section: Resultsmentioning
confidence: 99%